2014
DOI: 10.1016/j.jtcvs.2014.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tricuspid regurgitation in patients with hypoplastic left heart syndrome undergoing tricuspid valvuloplasty

Abstract: TR in patients with HLHS commonly emanates from the AS commissure. The associated mechanisms are often annular dilatation and anterior leaflet prolapse. Preoperative anterior leaflet prolapse was associated with worse outcomes. Annuloplasty, closure of the AS commissure, and repositioning of the anterior papillary muscle are effective in addressing TR in the short- and mid-term in this challenging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…In contrast, in the Boston Children's experience, 48% of patients required tricuspid valve re-repair and freedom from transplant or tricuspid valve replacement was 97% with a median follow-up of 38 months. 27 Despite a concerted effort by surgeons to preserve native valves with valvuloplasty in almost all circumstances, there are some valve pathologies that are simply beyond repair. A recent study of atrioventricular replacement among Japanese single-ventricle patients reported poor outcomes, with 20 of the 56 patients dying within a median 5.0-year follow-up and an almost 50% mortality among the 11 patients who required redo valve replacements.…”
Section: What's Badmentioning
confidence: 99%
“…In contrast, in the Boston Children's experience, 48% of patients required tricuspid valve re-repair and freedom from transplant or tricuspid valve replacement was 97% with a median follow-up of 38 months. 27 Despite a concerted effort by surgeons to preserve native valves with valvuloplasty in almost all circumstances, there are some valve pathologies that are simply beyond repair. A recent study of atrioventricular replacement among Japanese single-ventricle patients reported poor outcomes, with 20 of the 56 patients dying within a median 5.0-year follow-up and an almost 50% mortality among the 11 patients who required redo valve replacements.…”
Section: What's Badmentioning
confidence: 99%
“…The mechanism of tricuspid regurgitation in patients with HLHS remains complex and multifactorial: structural abnormalities of the tricuspid valve (TV) and functional causes such as RV dysfunction and dilatation of the TV annulus contribute to this problem. Morphology of the TV preoperatively such as anterior leaflet prolapse is known to be associated with worse outcome (24). …”
Section: The Right Ventricle In Patients With Hypoplastic Left Heart mentioning
confidence: 99%
“…The major findings of this paper are the following: Leaflet pathology associated with TR in patients requiring surgery has been described by both surgical review and echocardiography assessment with leaflet prolapse commonly described. 3 Our study is the first to quantify individual leaflet prolapse and tethering in this patient population to assess for TR mechanisms prior to repair. We identified prolapse of the TV, especially the anterior leaflet as associated with requirement for TV repair.…”
Section: Discussionmentioning
confidence: 99%
“…Success rates of TV repair with current surgical techniques are modest with significant numbers of patients with residual TR after surgical repair. 2,3 Determining pre-operative risk factors for poor results may allow for improvements and innovations in surgical techniques, however current data in HLHS for predictors of TV repair success is limited.…”
Section: Successful Vs Unsuccessful Repair -Preoperative Features and Suboptimal Outcomementioning
confidence: 99%
See 1 more Smart Citation